The Impact of Quizlet Learning Media in Increasing Student Interest and Motivation in Junior High School - Siswandi Siswandi; Hazlina Abdullah; Windy Zeanly Solisa; Haris Danial; Sri Winarti (International Journal of Language and Ubiquitous Learning, 2024)
Background. Lately, the influence on student learning motivation has begun to decline due to the lack of teacher mastery of learning media, even though at this time there are many references that can be used as guidelines or references in the process of introducing learning materials, for example by using online application-based learning media. Purpose. The purpose of this study was to determine the impact of quizlet learning media in increasing students' interest and motivation to learn in junior high school. This learning media can develop skills in reading and writing vocabulary. Method. This research method uses quantitative methods, data obtained through interviews and distributing questionnaires using Google Form. Results. The results of this study indicate that the implementation of the quizlet application can help millions of junior high school students in learning online, so that it can increase the value in the learning process to the maximum. Conclusion. The conclusion of the study can be concluded that students' understanding in the addition of vocabulary increased from before the application of learning with the quizlet application.